2013
DOI: 10.1055/s-0033-1333720
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Training Week on Heart Rate Variability in Elite Youth Rugby League Players

Abstract: The aim of this study was to examine the influence of weekly training including a competitive game on heart rate (HR) variability (HRV). Youth players (n=9, age 17-20 years) were monitored during daily supine rest (10 min) and standing (8 min), 5 times over 8 days. Heart rate recordings were analysed for time domain, frequency (e. g. low frequency [LF], high frequency [HF]) domain and non-linear measures of HRV and compared using ANOVA or Friedman's tests. Relationships between HRV and training workloads were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 28 publications
6
39
0
Order By: Relevance
“…Previous work in elite gymnastics, rugby and rowing have also found correlations with various measures of HRV and daily/total training load using session ratings of perceived exertion. [28][29][30] Although limited HRV data exists in team sports, the use of vagal related HR indices with endurance athletes is more extensive. 4,31,32 Indeed, based on data derived from endurance sports it is suggested that the use of one single data point could be misleading for practitioners due to the high day-to-day variation in these indices.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work in elite gymnastics, rugby and rowing have also found correlations with various measures of HRV and daily/total training load using session ratings of perceived exertion. [28][29][30] Although limited HRV data exists in team sports, the use of vagal related HR indices with endurance athletes is more extensive. 4,31,32 Indeed, based on data derived from endurance sports it is suggested that the use of one single data point could be misleading for practitioners due to the high day-to-day variation in these indices.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, ultra-short-lnRMSSD procedures facilitate more frequent monitoring due to less time requirements from athletes compared to traditional methodology and thus, enhance the practical usefulness of this tool in the field. More frequent data collection of lnRMSSD enables coaches to more effectively guide programming for athletes by manipulating training loads (Kiviniemi et al, 2007), detect fatigue and overreaching (Le Meur et al, 2013; Plews et al, 2012), evaluate training adaptations (Boullosa et al, 2013); and assess recovery status from training and competition (Bricout et al, 2010; Edmonds et al, 2013). Lastly, in the present study the relationship between the lnRMSSD and its delta changes was not correlated with changes in physical performance.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the small simple size, common in studies with elite athletes (Edmonds et al, 2013;Abad et al, 2014), the intraand intergroup comparisons of HRV indices were assessed using magnitude-based inferences (MBI) (Hopkins et al, 2009). Natural log-transformations (ln) of all HRV indices were log-transformed prior to analysis to reduce bias arising from non-uniformity of error.…”
Section: Discussionmentioning
confidence: 99%